Assess Drug Shortages' Effects on Health System Pharmacies - Ohud Khalid Ahmad Tirad; Howra Zaki Alabdulla; Ayed Shaleh Mubark Alshahrani; Sultan Abdullah Mubarak Al Dawsari; Rajeh Hadeel Qashan Alsubaie; Mubarak Hader Al Motawa; Abdullah Mubarak Masoud Alshahrani; Alghamdi, Abdulrahman Mohammed Abdulrahman; Raed Mohamed Jomaan Alzahrani; Ahed Mohammed Algarfan (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Drug shortages have become a significant issue globally, with the number of drugs in short supply rising dramatically over the past two decades. These shortages affect essential medications, including chemotherapy agents, anesthetics, and antibiotics, and are attributed to factors such as production disruptions and supply chain issues. The consequences of shortages impact patient care, clinical outcomes, and healthcare costs, placing additional strain on pharmacy personnel and healthcare systems. Methods: A 34-question electronic survey was distributed to pharmacy directors across multiple states to assess the impact of drug shortages in hospitals and health systems. The survey collected data on strategies for managing shortages, communication methods, staffing needs, and medication errors associated with shortages. A total of 219 responses were received, yielding a 40% response rate. Results: The survey revealed that 51% of hospitals monitored drug shortages, with significant price increases noted by 84% of respondents due to supply shortages. The average additional staff hours required to manage shortages ranged from 10 to 20 hours per week. A majority of respondents (76%) reported preapproval for auto-substitution of drugs in short supply, and 60% agreed that shortages created unsafe conditions for patients and staff. Respondents estimated an average of 1% to 5% medication errors due to shortages. Conclusion: Drug shortages continue to pose a major challenge for hospitals, requiring significant pharmacy resources and negatively affecting patient care. Pharmacists play a critical role in mitigating the impact of shortages through strategies such as auto-substitution, managing expiring medications, and coordinating with manufacturers. To address the ongoing issue, hospitals should consider adopting these strategies, and pharmacy education should include formal training on managing drug shortages. Collaboration between healthcare professionals, manufacturers, government agencies, and patients is essential to advocate for solutions to the drug shortage crisis.